Influence of the form and size of the isolated foundations on the stress-strain state of the soil base - Glushkov, Alexey; Bartolomey, Leonid; Glushkov, Vyacheslav (Journal of Applied Engineering Science, 2016)
This article reviews the investigations of the stress-strain state of the foundation bed under the variously shaped footings. The foundation basis is featured by cohesive and non-cohesive soil. Construction regulations do not allow to estimate the stress-strain state of bases with the complex shape of the bed.The article presents qualitative and quantitative stress-strain state changes of shape modification of the drawings. Research indicates the behavior of soil under the complex form foundation, components of displacements and stress isolines are also presented. А special attention is given to the assessment of the scale factor influence on the stress-strain state in the basis of the cross-shaped foundation.This article seems to be interesting to those who work in the field of building construction and geotechnics engineering.
Keywords: scale factor; stress-strain analysis; three rayed; cross-shaped; cruciform; foundation form